Strategi Telemarketing dalam Meningkatkan Keputusan Pembelian Aplikasi Trustmedis - Retno Nurul Solichah; Reiga Ritomiea Ariescy (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Telemarketing is a direct marketing method used by companies to reach customers by telephone. This strategy is considered very efficient because it allows companies to promote their products or services directly to consumers without having to meet the customers in person. PT Inovasi Teknologi Solusindo, known as Trustmedis, is one of the companies engaged in the health technology sector. This company provides software solutions based on Electronic Medical Records (EMR) for health facilities. This study uses a qualitative method with an observational approach. Data collection was carried out directly in the field while the author was undergoing an MBKM Internship at PT. Inovasi Teknologi Solusindo (Trustmedis) from August to December 2024. The results of the study, the telemarketing strategy at PT. Inovasi Teknologi Solusindo (Trustmedis) has been running well because of the benefits felt by customers from telemarketing carried out by Trustmedis, as well as the information provided that can increase customer knowledge about the products offered.